APPLE BREEDING PROGRAMS AND METHODS: THEIR DEVELOPMENT AND IMPROVEMENT - E. N. Sedov (Вавиловский журнал генетики и селекции, 2015)
Long-term studies of apple development features allowed breeding intensification and shortening of the time of cultivar development from 36–48 years to 23–27 or even 13–17 years. It is noted that requirements for cultivar are constantly toughened. They include high fitness, early maturation, performance, large size of fruits (140–160 g), thin and firm skin without rust signs or waxing; absence of abscission, sugar content no less than 12 %, ascorbic acid content about 30 mg/100 g. The preservation capacity of winter varieties must be no less than 7–8 months (Kichina, 2011). A perfect cultivar is impossible, because cultivar requirements change faster than the time required for breeding, but we should aspire to it.As a result of long-term breeding for the improvement of fruit biochemical composition, we managed to raise cultivars with high contents of P-active substances (up to 400–600 mg/100 g), but cultivars with the desirable content of ascorbic acid 25–30 mg/100 g have not been developed so far.A number of apple cultivars resistant to scab (bearing the Vf gene) have been developed in Russia. However, it is in prospect to develop cultivars with longer resistance on a digenic base combining genes Vf and Vr , Vf  and Vm , etc. It is necessary to create cultivars immune and highly resistant to powdery mildew, European red mite, apple moth, and other pests. We need apple cultivars with multiple resistance to pests and diseases.Apple breeding on a polyploidy level at the Institute of Fruit Crop Breeding proved to be quite promising. For the first time in Russia, triploid apple cultivars were obtained from different chromosome crossings 2x × 4x and 4x × 2x. They are notable for more regular fruit-bearing, high marketability of fruit and higher autogamy. This direction in breeding must be developed in the future.Columnar apples developed at Russian research institutes are of interest for fruit-growing intensification. They are valuable in amateur gardens, first of all. Breeders have to develop columnar, scab-resistant and triploid apple cultivars with high quality fruit.In the future, breeding should be aimed at developing cultivars for true-rooted apple and autogamous cultivars with the use of apetalous plants.With regard to the global climate warming, it may become necessary to revise the range of apple varieties and directions in breeding.